2007
DOI: 10.1093/nar/gkm706
|View full text |Cite
|
Sign up to set email alerts
|

Structure of two intramolecular G-quadruplexes formed by natural human telomere sequences in K + solution †

Abstract: Intramolecular G-quadruplexes formed by human telomere sequences are attractive anticancer targets. Recently, four-repeat human telomere sequences have been shown to form two different intramolecular (3 + 1) G-quadruplexes in K+ solution (Form 1 and Form 2). Here we report on the solution structures of both Form 1 and Form 2 adopted by natural human telomere sequences. Both structures contain the (3 + 1) G-tetrad core with one double-chain-reversal and two edgewise loops, but differ in the successive order of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

40
602
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 494 publications
(648 citation statements)
references
References 58 publications
40
602
0
6
Order By: Relevance
“…In 2002, a crystal structure of the parallel-stranded G-quadruplex was reported using a 22-nt human telomeric sequence in the presence of K + [47]. Recent results have shown that hybrid-type intramolecular Gquadruplexes ( Figure 2A) appear to be the predominant conformation formed in human telomeric sequences in K + solution [48][49][50][51][52][53][54][55]. The hybrid-type structures are distinct from the Na + -structure in solution ( Figure 2B) and the crystal structure in the presence of K + ( Figure 2C).…”
Section: Introductionmentioning
confidence: 99%
“…In 2002, a crystal structure of the parallel-stranded G-quadruplex was reported using a 22-nt human telomeric sequence in the presence of K + [47]. Recent results have shown that hybrid-type intramolecular Gquadruplexes ( Figure 2A) appear to be the predominant conformation formed in human telomeric sequences in K + solution [48][49][50][51][52][53][54][55]. The hybrid-type structures are distinct from the Na + -structure in solution ( Figure 2B) and the crystal structure in the presence of K + ( Figure 2C).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, NMR-based studies in KCl solution show that the same sequence folds predominantly to the hybrid-1 and hybrid-2 structures (Fig. 1A) (5)(6)(7)(8). Characteristics of this structure are an antiparallel strand orientation with a 3+1 core of syn and anti G nucleotides yielding three tetrads.…”
mentioning
confidence: 95%
“…Of particular interest recently are the conformations available to G-rich DNAs which are designated as G-quadruplexes. DNA sequences that have islands of G 2-4 separated by 1 to 4 A and/or T bases can form a rich library of secondary structures with different molecularities, strand orientations, and guanine base conformation (i.e., syn or anti) [3][4][5][6][7][8][9][10][11][12][13][14]. The conformations and their stabilities are highly dependent upon the sequence context and buffer conditions [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…A model was presented for the quadruplex to random coil transition, via formation of an unknown intramolecular intermediate, with exclusion of K + during each transition. Review of the literature reveals that different investigators have used slight variations of the sequence (TTAGGG) 4 for their investigations and have drawn conclusions based upon their data [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. We recently reported however that changing just one base in just one loop of the folded quadruplex influences both conformation and stability [20].…”
Section: Introductionmentioning
confidence: 99%